Isolation improvement in UWB-MIMO antenna system using slotted stub - Altaf, Ahsan; Iqbal, Amjad; Smida, Amor; Smida, Jamel; Althuwayb, Ayman A.; Hassan Kiani, Saad; Alibakhshikenari, Mohammad; Falcone, Francisco; Limiti, Ernesto (MDPI, 2020)
Multiple-input multiple-output (MIMO) scheme refers to the technology where more than one antenna is used for transmitting and receiving the information packets. It enhances the channel capacity without more power. The available space in the modern compact devices is limited and MIMO antenna elements need to be placed closely. The closely spaced antennas undergo an undesirable coupling, which deteriorates the antenna parameters. In this paper, an ultra wide-band (UWB) MIMO antenna system with an improved isolation is presented. The system has a wide bandwidth range from 2-13.7 GHz. The antenna elements are closely placed with an edge to edge distance of 3 mm. In addition to the UWB attribute of the system, the mutual coupling between the antennas is reduced by using slotted stub. The isolation is improved and is below -20 dB within the whole operating range. By introducing the decoupling network, the key performance parameters of the antenna are not affected. The system is designed on an inexpensive and easily available FR-4 substrate. To better understand the working of the proposed system, the equivalent circuit model is also presented. To model the proposed system accurately, different radiating modes and inter-mode coupling is considered and modeled. The EM model, circuit model, and the measured results are in good agreement. Different key performance parameters of the system and the antenna element such as envelope correlation coefficient (ECC), diversity gain, channel capcity loss (CCL) gain, radiation patterns, surface currents, and scattering parameters are presented. State-of-the-art comparison with the recent literature shows that the proposed antenna has minimal dimensions, a large bandwidth, an adequate gain value and a high isolation. It is worth noticeable that the proposed antenna has high isolation even the patches has low edge-to-edge gap (3 mm). Based on its good performance and compact dimensions, the proposed antenna is a suitable choice for high throughput compact UWB transceivers.
Keywords: Isolation Enhancement; Surface Waves; Gain; Circuit Model; Slotted-Stub; MIMO Antennas